Cognitive and non-cognitive core curriculum for undergraduate education for business and management in South Africa and the USA - Ficker, A. B. D.(Albert Bernhard Daniel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1988.